Comparing the healing effects of arnebia euchroma ointment with petrolatum on the ulcers caused by fractional CO2 laser : a single-blinded clinical trial - Yusufi, Maryam; Nasiri, Muhsin; Barati, Maryam; Muhsini Mughaddam, Parvaneh; Hasheminejad, Sayyid Abbas; Nami, Husayn Ismailzad; Barikbin, Behrooz; Khoshzaban, Fariba; Aliasl, Fatimah; Aliasl, Jale; Talei, Daryush; Razzaghi, Zahra; et al. (Iranian red crescent medical journal, 2014)
Background : Arnebia euchroma ointment (AEO) has been used in Iranian traditional medicine for burn wound healing. Objectives : The aim of this study is to evaluate wound healing efficacy of AEO in burn wounds after fractional Co2 laser. Patients and Methods : This split-face, single-blinded, single-center clinical study was performed in Shohada-e-Tajrish Hospital, Tehran, Iran. A total of 26 subjects with facial acne scar, who were to receive fractional CO2 laser resurfacing were recruited. After laser procedure, AEO was applied to one side of the face and petrolatum on the other side for wound healing. Digital photographs were taken from acne scar area before resurfacing and on each of the assessment sessions. Three researchers, who were unaware of the applied medications, assessed these digital photographs for erythema, edema, epithelial confluence, crusting / scabbing, and general wound appearance. Subject’s irritations such as dryness and itching were evaluated on the second, fifth, and seventh days. Results : Our study indicated higher epithelial confluence and general wound appearance scores (P = 0.045 for both) and less erythema and edema on fifth day in petrolatum (P = 0.009 and P = 0.034, respectively). The results showed less crusting and erythema (P = 0.016 and P = 0.035, respectively) and higher general wound appearance scores in petrolatum on the second day (P = 0.035 and P = 0.001, respectively). Dryness was the most common subjective complaint in both groups; however, it was more severe in AEO, especially on the second day (P = 0.023). Conclusions : Despite the healing effects of AEO in burn wounds, petrolatum was more effective than AEO in post-laser wound.